Noise Testing And Analysis of Two Wheelers - Chitkara, Karan (My University, 2009)
The number of vehicles like motor-cycles, cars, trucks and scooters etc. are increasing day by day which create large amount of noise on highways and street systems. The purpose of this work is to study the fundamentals of noise and analysis of two wheeler noise which causes serious effects on human beings. So, it is necessary to study the Two Wheeler noise: 1) Present thesis work is completed using four basic methods of monitoring: a) Pass by test b) Parallelepiped Method for calculating acoustic power. c) Frequency analyzer d) Motorway noise predicting method. First method has been used for the measurement of Sound Pressure Level at two operating conditions 3rd and 4th Gear. Second method has been used for calculating acoustic power at two operating conditions Zero and Full Throttle. Third method has been used to analyze the variation in Sound Pressure Level with frequency at two operating condition Zero and Full Throttle . Fourth method has been used to analyzed predicted mean energy emission Level for 10 sec at different speeds. This work also includes use of Capacitor Microphone to perform acoustical measurements in accordance with ISO standards and recommendations. Further the basic method for pass by test, sound power level measurement with sound pressure level, frequency analysis and motorway noise prediction model have been described with the experimental work. This kind of present work on noise has been carried out for the first time in Mechanical Engineering Department, Thapar University, Patiala.
M.E. (CAD/CAM and Robotics)
Keywords: Noise; Two-wheelers; pass by test